2015
DOI: 10.1021/jp512776p
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Reductive Sintering of Nickel Oxide Nanoparticles under Ambient Conditions

Abstract: This work is concerned with the kinetics of laser-induced reductive sintering of nonstoichiometric crystalline nickel oxide (NiO) nanoparticles (NPs) under ambient conditions. The mechanism of photophysical reductive sintering upon irradiation using a 514.5 nm continuous-wave (CW) laser on NiO NP thin films has been studied through modulating the laser power density and illumination time. Protons produced due to hightemperature decomposition of the solvent present in the NiO NP ink, oxygen vacancies in the NiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 54 publications
1
52
0
Order By: Relevance
“…Furthermore, liquid-phase PLA permits the collection of synthesized nanoparticles much more easily than PLA in vacuum. Many researchers have reported the formation of unique nanoparticles by changing the liquid medium or by adding some chemical compounds into the medium [22,23,25,27]. Namely, this superimposes the chemical reactivity of the liquid onto the physical process of laser ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, liquid-phase PLA permits the collection of synthesized nanoparticles much more easily than PLA in vacuum. Many researchers have reported the formation of unique nanoparticles by changing the liquid medium or by adding some chemical compounds into the medium [22,23,25,27]. Namely, this superimposes the chemical reactivity of the liquid onto the physical process of laser ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ag[3a,13] and Cu grids have emerged as next‐generation flexible transparent conductors owing to their high conductivities, high transmittances, and low processing temperatures. In the recent study,[8b] Ni electrode grids on a glass substrate were demonstrated as a transparent conducting panel for touch screen application. However, the Ni electrode grids failed to concurrently satisfy transparency and flexibility since PI is the only applicable flexible substrate, as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] Using thermal and chemical energy, electrons and metal ions are separated, and metals are extracted through combination of separated electrons and metal ions. [ 21,22 ] Such reduction process is being widely applied for diverse metallic oxides (TiO 2 , NiO, GO, Cu x O) to convert oxides into their metallic counterparts, [23][24][25][26] however, the existing processes are limited to nanoparticles (NPs). In the NP reduction process, the target NPs are not only reduced, but also merged together simultaneously by the applied large thermal energy.…”
Section: Doi: 101002/adma201503244mentioning
confidence: 99%